(3EOGQI GdeaGhVGJ s - (3eUWai jhSa(B, (3cGajs ((3YeGf (B:s (3OGQ GdMGeO ddfTQ hGdJhRjY(B,s, 2015)
(3eaghe GdJaGhV hNUGFUg, NWhGJ heMOOGJ GdfLGM aj GdJaGhV, CfhGY GdJaGhV hCSGdjHg, GdVhGHW GdJaGhVjI, GdUQGY hGdCSGdjH GdJaGhVjI, SjGSGJ GdJaGhV, GdEYOGO ddJaGhV, NUGFU GdeaGhV GdaYGd(B-(3CfeGW GdeaGhVjf hcjajI GdJYGed eY cd feW, GSJQGJjLjGJ hJcJjcGJ GdJaGhV, GdUaGJ hGdegGQGJ GdQFjSjI ddeaGhV GdfGLM,GdYhGed GdeDKQI aj GdYedjI GdJaGhVjI, GdOHdheGSjIs
(3HjHdjhZQGajG(B: (3U U(B219-221s
Keywords: (3EOGQI GdCYeGds; (3GdeaGhVGJs